2023
DOI: 10.1038/s41467-023-37463-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing brain dynamics during ketamine-induced dissociation and subsequent interactions with propofol using human intracranial neurophysiology

Abstract: Ketamine produces antidepressant effects in patients with treatment-resistant depression, but its usefulness is limited by its psychotropic side effects. Ketamine is thought to act via NMDA receptors and HCN1 channels to produce brain oscillations that are related to these effects. Using human intracranial recordings, we found that ketamine produces gamma oscillations in prefrontal cortex and hippocampus, structures previously implicated in ketamine’s antidepressant effects, and a 3 Hz oscillation in posterome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…In addition, patients under ketamine did not experience cognitive decline after surgery and did not report amnesia for this part of the surgery. These findings are similar to previous results reported in the literature 44 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, patients under ketamine did not experience cognitive decline after surgery and did not report amnesia for this part of the surgery. These findings are similar to previous results reported in the literature 44 …”
Section: Discussionsupporting
confidence: 93%
“…Ketamine acts via NMDA receptors and HCN1 channels, resulting in enhanced neural activity and specific brain oscillations. Human intracranial recordings revealed that ketamine produces γ oscillations in the prefrontal cortex and hippocampus, along with Δ oscillations in the posteromedial cortex, which contribute to its dissociative effect 44 . Our study demonstrates an increase in low γ and a decrease in Δ/θ oscillatory cortical activity in prefrontal EEG recordings during ketamine administration, consistent with previous research 14,45 .…”
Section: Discussionsupporting
confidence: 90%
“…Ketamine can also alter hyperpolarization-activated nucleotide-gated (HCN) channels [18] for slowdelta oscillatory contributions. In fact, low doses of ketamine have been found to produce 3 Hz oscillations in posteromedial cortex [3, 12]. These 3 Hz oscillations have been found to rely on HCN channels [3].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ketamine has been proposed to preferentially antagonize NMDA receptors of inhibitory neurons to drive a surge in excitation [6, 911]. It is in this disinhibited brain state that the oscillatory dynamics have been characterized [1, 3, 12]. However, taking into account this disinhibition, it remains unknown how the action of ketamine at the subcellular level can give rise to the oscillatory dynamics at the network level.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting feature of Type 2 networks is that they may be relevant to the kind of gamma oscillation induced by drugs like Ketamine. Ketamine is known to induce profound changes in brain oscillatory dynamics that appear to be correlated with its antidepressant and sensory dissociative activity (Tian et al 2023). The electrophysiological profile of sub-anesthetic doses of Ketamine generally includes an increase in gamma oscillation power and a decrease in delta, alpha, and beta oscillation power ( instead of those on excitatory neurons, therefore reducing interneuron activity and leading to a disinhibition effect on the overall network activity.…”
Section: Discussionmentioning
confidence: 99%